Comprehensive characterization of lotus root polysaccharide-phenol complexes - Yi, Yang; Tang, Hao-Su; Sun, Ying; Xu, Wei; Min, Ting; Wang, Hong-Xun (Food chemistry, 2022)
•Phenolic compounds had different affinities to lotus root polysaccharides (LRPs).•Phenolic binding changed the molecular weight and aggregation behavior of LRPs.•Phenols increased the antioxidant activity of LRPs in a binding ratio-dependent way.•Catechin-bound LRPs had a dual role in macrophage immunomodulation. To explore the effects of phenolic binding on the structure and activity of lotus root polysaccharides (LRPs), five LRP-phenol complexes containing catechin (61.22 mg/g), gallic acid (9.37 mg/g), ferulic acid (29.28 mg/g), chlorogenic acid (83.80 mg/g) or caffeic acid (14.80 mg/g) were prepared via noncovalent intermolecular interaction, respectively. The interaction was confirmed by the differences among LRPs, phenols and their complexes in ultraviolet–visible and Fourier-transform infrared spectra. The phenolic binding caused significant changes in the molecular weight (MW) distribution and aggregation behavior of LRPs, particularly their average MW (34.49 kDa) increased by 3.73–8.30 times. Compared to LRPs, the complexes all showed stronger antioxidant activities. Notably, the binding of catechin improved the macrophage-stimulating effect of LRPs, specifically promoting the NO production at normal condition and inhibiting the NO overproduction induced by lipopolysaccharide. The noncovalent interaction with phenolic compounds is a promising method for the structural and functional improvement of LRPs.